PALEOBIOGEOGRAFIA Y EDAD DE LA FAUNA DE MAORITES- GUNNARITES (AMMONOIDEA) DEL CRETACICO. SUPERIOR DE LA ANTARTIDA Y PATAGONIA. (Ameghiniana, 2014)
Maorites and Gunnarites predominate among the youngest Cretaceous ammonite faunas of Patagonia and the Antarctic Peninsula. Because these genera are strongly endemic, zonations based on them have had only local validity. The family Pachydiscidae, which had an almost world-wide distribution, provides a better basis to establish a zonation. In the Vicecomodoro Marambio (Seymour) Island (Antarctic Peninsula) the ammonite fauna, including Maorites spp., is subdivided here into three zones on the basis of first occurences of species of Pachydiscus: P. (P.) ootacodensis (Stoliczka); P. (P.) "aff. gollevillensis d'Orbigny"; and P. (P.) sp. nov. Similarities with other Indopacific and European faunas as well as associations wjth foraminifera and calcareous nannoplankton, indicate an age ranging from latest Campanian-earliest Maastrichtian to late Maastrichtian for these three zones. In Patagonia and Antarctica, Maorites has an age ranging from possibly the early-middle Campanian to the late Maastrichtian. However several of the older occurrences are doubtful, and the maximum development of this genus is attained in beds dated independently as Maastrichtian. Gunnarites is more abundant in lower levels than Mao rites, and its occurrence in Antarctica Is interpreted to be typical of the middle to late Campanian, but in Patagonia it.might extend to the Maastrichtian.